2021
DOI: 10.3390/ma14092126
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Ferroelectric Phase in Highly Oriented Quinuclidinium Perrhenate (HQReO4) Thin Films

Abstract: The low-temperature processability of molecular ferroelectric (FE) crystals makes them a potential alternative for perovskite oxide-based ferroelectric thin films. Quinuclidinium perrhenate (HQReO4) is one such molecular FE crystal that exhibits ferroelectricity when crystallized in an intermediate temperature phase (ITP). However, bulk HQReO4 crystals exhibit ferroelectricity only for a narrow temperature window (22 K), above and below which the polar phase transforms to a non-FE phase. The FE phase or ITP of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Several systems containing variations of the quinuclidinium molecule have been studied in recent years. ,,,, ,, Notably, Tang et al reported a Curie temperature of 466 K for [F-C 7 H 13 N]­ReO 4 . Another material of interest is [C 7 H 14 N]­IO 4 , for which You et al found 12 equivalent directions of polarization .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several systems containing variations of the quinuclidinium molecule have been studied in recent years. ,,,, ,, Notably, Tang et al reported a Curie temperature of 466 K for [F-C 7 H 13 N]­ReO 4 . Another material of interest is [C 7 H 14 N]­IO 4 , for which You et al found 12 equivalent directions of polarization .…”
Section: Resultsmentioning
confidence: 99%
“…Several systems containing variations of the quinuclidinium molecule have been studied in recent years. 6,18,21,28,[67][68][69]81,82 17 The reported coercive fields of these Table 2. continued a Values have been listed for the melting temperatures T melt.…”
Section: Resultsmentioning
confidence: 99%
“…The design and development of new, highly efficient systems for food industry [ 1 , 2 ], electronic [ 3 , 4 ], information science [ 5 , 6 ] biomedicine [ 7 , 8 ] and environmental [ 9 , 10 ] applications constitute an important challenge. For such ambitious purpose it is mandatory to choose ecofriendly materials or recyclable ones, showing wide versatility in terms of structure and physicochemical properties [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%